2020
DOI: 10.1038/s41598-020-59400-w
|View full text |Cite
|
Sign up to set email alerts
|

Bit type exerts an influence on self-controlled rein tension in unridden horses

Abstract: Bit configuration and acting rein forces play a crucial role in oral health and comfort of ridden horses. Although it is a big animal welfare issue, dynamic response of horses to different bits has yet not been thoroughly investigated. This convenience sample experimental study describes a model to overcome the almost uncontrollable influence of riders on rein tension and evaluates self-controlled maximum side rein tension of ten sound horses randomly bitted with a double-jointed (DJS) and a version of a Mulle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Snaffle‐bitted racehorses had more lesions than did gag‐bitted polo ponies, 2 and 11‐mm Myler‐bitted ridden horses were less stressed and expressed less head‐tossing than horses ridden with a traditional 18‐mm snaffle bit 8 . Unridden horses on a treadmill independently applied higher rein tension with a double‐jointed bit compared with an unjointed but curved mullen mouth snaffle bit 9 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Snaffle‐bitted racehorses had more lesions than did gag‐bitted polo ponies, 2 and 11‐mm Myler‐bitted ridden horses were less stressed and expressed less head‐tossing than horses ridden with a traditional 18‐mm snaffle bit 8 . Unridden horses on a treadmill independently applied higher rein tension with a double‐jointed bit compared with an unjointed but curved mullen mouth snaffle bit 9 …”
Section: Introductionmentioning
confidence: 97%
“…8 Unridden horses on a treadmill independently applied higher rein tension with a double-jointed bit compared with an unjointed but curved mullen mouth snaffle bit. 9 Horses can be controlled without a bit during exercise, 10 but bitting is considered an obligatory safety measure in harness racing.…”
Section: Introductionmentioning
confidence: 99%
“…The two spikes within each stride are, however, often different in magnitude. A study using side reins reported a single large spike in the rein ipsilateral to the forelimb as it leaves the ground coordinated with a smaller spike in the contralateral rein [8]. The graph shown in Figure 1 has a higher spike in the rein ipsilateral to the forelimb leaving the ground and a smaller spike in the contralateral rein.…”
Section: Basic Characteristics Of the Rein Tension Signalmentioning
confidence: 94%
“…The graph shown in Figure 1 has a higher spike in the rein ipsilateral to the forelimb leaving the ground and a smaller spike in the contralateral rein. This may relate to the fact that walking horses display some lateral movement of the head between left and right forelimb stance phases [8] and that when side reins are used, there is no compensation for asynchronous changes in tension as there might be with a rider.…”
Section: Basic Characteristics Of the Rein Tension Signalmentioning
confidence: 99%
See 1 more Smart Citation